Treatment of Pulp Factories Wastewater Containing Chlorophenolic Compounds with Ozonation - Hajiali, Amir; Pirumyan, Gevorg; Reza Sharif Vaghefi, Hamid; Shahmiri, Masoud (Asian Journal of Chemistry, 2012)
In this research, a comparison between biological treatment and a combination of that with ozonation treatment is studied. Wastewater arising from pulp factories has toxic and poisonous materials, which make some serious environmental problems and that is for containing specific poisonous chlorophenolic compounds that in biological reactors in a liquid phase can be absorbed much easier and with a higher rate. Because of high molecular weight of these toxic compounds the treatment is performed in a sequential process to make these compounds smaller and change to dissolvable substances in the environment. Through this way the quality of treatment and the value of dissolvable substances, which can be returned to the environment are increased. A remarkable reduction of chemical oxygen demand, total organic carbon and adsorbable organically bound halogens in this treatment system in comparison with the most common biological treatment system is achieved.